Penerapan Kartu Memory Listening Berbasis Problem Based Learning Upaya Peningkatan Sikap Kritis dan Keterampilan Menyimak Informasi Murid Kelas III - Maharani, Elsa; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Listening skills for aural texts among elementary school students remain relatively low, as reflected in their suboptimal ability to identify essential information, grasp the main message, and provide logical responses to spoken texts. Although listening instruction has been widely studied, research that specifically integrates concrete audiolingual media with the Problem-Based Learning (PBL) model remains limited. This study aimed to describe the implementation of Kartu Memory Listening media within a PBL framework in listening instruction and to examine its effectiveness in improving students’ listening skills and critical reasoning. A mixed-methods approach with an embedded concurrent design was employed, involving 28 third-grade students selected through purposive sampling. Listening skills data were collected using pretest–posttest assessments with teacher-read announcement stimuli supported by teacher cards, while students used learner cards containing characteristics and keywords of various types of announcements along with visuals of four common public locations (stations, ports, airports, and bus terminals). Critical reasoning was assessed through observations conducted by two observers using a standardized instrument. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using the Miles–Huberman technique. The results show a significant improvement in listening skills, with a mean posttest score of 91.6 (very good category), and in critical reasoning, with a score of 87.5 (good category). These findings enrich theoretical discussions on the use of concrete audiolingual media within a PBL framework and provide practical implications for Bahasa Indonesia instruction in elementary schools, while also opening avenues for further research on additional factors that may influence learning outcomes but were not examined in this study.